Urgensi Pembentukan Peraturan Perundang-Undangan Tentang Virtual Ofiice di Indonesia - purborini, vivi sylvia (Jurnal Administrasi Politik dan Sosial, 2024)
Technological advancement is the development of tools or working methods as an improvement in shortening the time to meet needs at any time. In the era of globalization like now, technological advancement is getting more and more rapid. This is due to various factors, such as increasing competition between countries, the need to improve the quality of life, or a series of equally aimed at seeking the truth in this sophisticated era. Research Methods The research used in writing this article is normative legal research and principles used in the discipline of law). Virtual office is a concept where a business or individual can run their operations remotely without the need to have a physical office space permanently. In Indonesia, regulations related to the use of virtual offices are not specifically regulated in one regulation.